Performance of Optimal Combining in UWA Communication - Tripathi, Anuj (My University, 2008)
For the underwater communication, acoustic waves are best solution besides Radio Frequency (RF) waves, Laser beams, Ultra Low Frequency (ULF), and optical cables. Acoustic waves need fairly low power for transmission and reception of signal and also small amount of hardware is needed. Underwater acoustic communication channels are characterized by a path loss that depends not only on the distance between the transmitter and receiver, as it is the case in many other wireless channels, but also on the signal frequency. The signal frequency determines the absorption loss which occurs because of the transfer of acoustic energy into heat. This fact implies the dependence of acoustic bandwidth on the communication distance. The absorption loss increases with frequency as well as with distance, eventually imposing a limit on the available bandwidth within the practical constraints of finite transmission power. Underwater acoustic (UWA) channels present a number of challenges to the designers of communications systems. One of their most important characteristics is multipath propagation, which severely limits data rate and system reliability. This thesis addresses the problem of multipath propagation in underwater acoustic channels and to combat with multipath diversity technique proposed in this thesis is Optimal Combining (OC). The Optimal combining (OC) scheme is investigated in detail. Other diversity combining schemes, such as maximum ratio combining (MRC), selection combining (SC) and equal gain combining (EGC) are outperformed by OC in the presence of number of interferers. First, the comparison of SC and MRC with OC in the absence of interferer for the bandwidth efficient modulation techniques (like M-array Phase Shift Keying (MPSK) and M-array Quadrature Amplitude Modulation (MPSK)) is considered in underwater acoustic channels. The output signal-to-noise ratio (SNR) expression is derived, and an expression for the bit error rate (BER) is determined. Simulations of the channels are performed and obtained results are compared. Then, derive and simulate the expressions for OC in the presence of number of interferers. OC receiver analysis is for varying diversity paths. Finally, OC is demonstrated in UWA environment and simulation results are given.
Keywords: Optimal Combining; Underwater Acoustic Communication